Sport Psychological Characteristics and Resilience in a Group of Surfers from Lima - Brozovich-Neyra, Cecilia (2024)
This study focused on analyzing the relationship between the psychological characteristics of sports and dimensions of resilience in a group of 200 surfers from Lima and Callao through a cross-sectional investigation with a quantitative approach and correlational design. The Psychological Inventory of Sport Performance (IPED) and the Scale of Resilience in the Sport Context (ERCD) were used to collect data. The results revealed significant and positive correlations between the dimensions of self-confidence, visuo-imaginative control, moti-vational level, positive coping control, and attitudinal control with a high effect of .32, .35, and .39, respectively. In addition, for the visuo-imaginative control and motivational level, their magnitude criteria were low with .28 and .27 respectively, which supports the hypotheses proposed. Likewise, in the analysis of the personal competence dimension of resilience, they show a high effect with a .89. Finally, an inverse correlation (-.22) was found between the negative coping dimension of the IPED and resilience, indicating that greater negative coping is related to less resilience in surfers. This study provides valuable information for understanding the psychological factors that can influence the performance and emotional well-being of surfers.